OC-006 Influence of BMI and Alcohol on Liver-Related Morbidity and Mortality in a Cohort of 108, 000 Women from the General Population from Ukctocs. (4th June 2013) - Trembling, P M; Apostolidou, S; Parkes, J; Ryan, A; Gentry-Maharaj, A; Tanwar, S; Menon, U; Rosenberg, W M
Abstract : Introduction: Alcohol and fat are major causes of chronic liver disease (CLD), however their relative influences are not well understood. We aimed to determine liver-related morbidity and mortality attributable to fat and alcohol by stratifying a cohort of 202, 638 women according to BMI and alcohol intake. Methods: 107, 742 women participating in the UK Collaborative Trial of Ovarian Cancer Screening where self-reported height, weight and alcohol intake were available were included. First episode related to cirrhosis (ICD-10 codes K70, K73, K74) either from inpatient Hospital Episode Statistics or death certificate was recorded following trial entry. Participants were stratified by low or high BMI ( < 25 or ≥25 kg/m2), low or high alcohol intake (0–15 or over 15 units/week) and combinations of these parameters. Results: Median age at recruitment was 60 years (50–75). Mean BMI was 26.4 kg/m2. There were 90 events (54 inpatient episodes and 36 deaths). There was no difference in risk of event between the BMI groups, however there was a significant increase in risk in the high alcohol group (Log-Rank < 0.001). Cox proportional hazards regression analysis (covariates age, smoking, BMI and alcohol intake), found that compared to the low BMI/low alcohol group, there was an incremental increase in risk of event in the high BMI/low alcohol, low BMI/high alcohol and high BMI/high alcohol groups respectively. However, only the combination of high BMI and high alcohol reached significance (table and figure ). Conclusion: These data indicate that the combination of high BMI and alcohol intake is associated with a synergistically increased risk of CLD. Alcohol may be the more significant contributing factor. Further work will define thresholds for each risk factor that independently and in combination increase CLD risk. Disclosure of Interest: None Declared